Patients and hospital managers want laparoscopic simulation training to become mandatory before live operating: a multicentre qualitative study of stakeholder perceptions. (21st March 2018) - Preshaw, Jessica; Siassakos, Dimitrios; James, Mark; Draycott, Timothy; Vyas, Sanjay; Burden, Christy
Abstract : Background: Surgical procedures are complex and susceptible to human error. Individual surgical skill correlates with improved patient outcomes demonstrating that surgical proficiency is vitally important for patient safety. Evidence demonstrates that simulation training improves laparoscopic surgical skills; however, projects to implement and integrate laparoscopic simulation into core surgical curricula have had varied success. One barrier to successful implementation has been the lack of awareness and prioritisation of simulation initiatives by key stakeholders. Objective: To determine the knowledge and perceptions of patients and hospital managers on laparoscopic surgery and simulation training in patient safety and healthcare. Method: A qualitative study was conducted in the Southwest of England. 40 semistructured interviews were undertaken with patients attending general gynaecology clinics and general surgical and gynaecology hospital managers. Results: Six key themes identified included: positive expectations of laparoscopic surgery; perceptions of problems and financial implications of laparoscopic surgery; lack of awareness of difficulties with surgical training; desire for laparoscopic simulation training and competency testing for patient benefit; conflicting priorities of laparoscopic simulation in healthcare; and drawbacks of surgical simulation training. Patients and managers were largely unaware of the risks of laparoscopic surgery and challenges for training. Managers highlighted conflicting financial priorities when purchasing educational equipment. Patients stated that they would have greater confidence in a surgeon who had undertaken mandatory surgical simulation training and perceived purchasing simulation equipment to be a high priority in the National Health Services. Most patients and hospital managers believed trainees should pass an examination on a simulator prior to live operating. Conclusions: Competency-based mandatory laparoscopic simulation was strongly supported by the majority of stakeholders to augment the initial learning curve of surgeons.